2022
DOI: 10.3390/ijerph192316190
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on the Mental Health of Urban Residents—Evidence from China

Abstract: Based on a nationwide micro-survey in China from 2018 to 2021, this paper empirically estimates the causal impact of the COVID-19 pandemic on the mental health of Chinese residents, by exploiting the distribution of the outflow population from Wuhan as an instrumental variable (IV). Our findings suggest that for every 10% increase in the cumulative confirmed cases, the number of mentally unhealthy days reported by urban residents in the past 30 days will increase by 2.19, an increase of 46.90% compared with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The coefficients of “The perceived rate of CHECS” and “Except for individuals, the utilization rate of CHECS” are significant at least at the 10% level in first-stage regression, and the Kleibergen-Paap rk Wald F-statistic is much larger than its critical value, which can exclude the possibility of weak IVs; the Hansen J-test p -value is greater than 0.1, which indicates that the null hypotheses cannot be rejected. That provides suggestive evidence that the variables are valid instruments ( 29 ). Comparatively, we discovered that the OLS estimates are in fact biased and that putative endogeneity tends to underestimate the beneficial effects of CHECS use on self-reported health.…”
Section: Resultsmentioning
confidence: 89%
“…The coefficients of “The perceived rate of CHECS” and “Except for individuals, the utilization rate of CHECS” are significant at least at the 10% level in first-stage regression, and the Kleibergen-Paap rk Wald F-statistic is much larger than its critical value, which can exclude the possibility of weak IVs; the Hansen J-test p -value is greater than 0.1, which indicates that the null hypotheses cannot be rejected. That provides suggestive evidence that the variables are valid instruments ( 29 ). Comparatively, we discovered that the OLS estimates are in fact biased and that putative endogeneity tends to underestimate the beneficial effects of CHECS use on self-reported health.…”
Section: Resultsmentioning
confidence: 89%
“…The results found in this study are similar to studies developed in India, United Kingdom, Germany and China that the pandemic was indicated as a negative factor for the mental health of the general population. Negatively affecting all aspects of individuals' lives and leaving them more vulnerable to the development of mental disorder problems, it can be seen that the pandemic has caused mental and physical damage, as well as leading to psychological conditions of medium and severe intensity, such as post-traumatic stress disorders, depression, anxiety, panic disorders and behavioral disorders [25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…A key aspect in this regard is the perception of entrapment, which modulates responses of greater or lesser severity and frequency of suicidality (Calati et al, 2023). However, it remains complex to predict which risk variables modulate the majority of suicide deaths, especially in populations with high social vulnerability, such as LGBTQ + people (Cruz et al, 2022).…”
Section: Introductionmentioning
confidence: 99%